Gayathri Mantra and Social Skills Training for Social Anxiety, Stress, Self Concept, and Well Being among School Students with Learning Difficulties - R, Sudha. (International Journal of Psychosocial Rehabilitation, 2020)
The Gayathri Mantra is a four-verse poem that was mentioned in epics of Hinduism and has been further researched for its lasting effect on mind and body. Here an attempt is being made to combine the healing effects of the Gayathri mantra along with social skills training for benefitting the often ignored psychological issues such as social anxiety, self-concept, and well-being faced by school students with learning difficulties.ObjectivesThe major objectives of the study are to understand the level of social anxiety, stress, self-concept, and well-being among school students with learning difficulties. An effort to improve the self-concept and well-being and to reduce the level of social anxiety and stress experienced using an intervention of social skills training along with the chanting/listening of the Gayathri Mantra with simple breathing exercises.MethodThe Liebowitz Social anxiety Scale (Liebowitz M R, 1987) was used to pretest the Social Anxiety levels. The Perceived Stress Scale for Children (White, B. P., 2014) was used to study the stress levels of students. The Self Concept Questionnaire (SCQ, Saraswat, R.K ) was used to pretest the self concept and the WHO Well Being Scale was used to pretest the well being among 80 school students of the age group 10 to 17 years. This group was then randomly divided into 2 groups of 40 members each, hence 40 students in the Experimental Group and 40 students in the waitlist Control Group. This was followed by an intervention of the Social Skills Training Module and the chanting/listening of the Gayathri Mantra for a duration of two months. A post-test was conducted and the results analyzed. A follow-up study was also conducted after two months.Results and conclusionsThe SPSS 21 version was used to analyze obtained data. Analysis showed that the intervention of social skills training and Gayathri Mantra was effective in reducing the social anxiety and stress levels of the experimental group. Also post-intervention, an improvement, especially in the self-concept, was observed in the students of the experimental group. The well-being level also shows improvement. These results were found to be maintained during the follow-up study. It can be effectively concluded that the intervention of social skills training with Gayathri Mantra is effective in reducing social anxiety and stress among students with learning difficulties. Also, the intervention helps to improve self-concept and well-being among the students.